Cho A = (x-4) - 3(x+1). Tìm x sao cho A = 4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(M(x) = A(x) + B(x) \\= 4{x^4} + 6{x^2} - 7{x^3} - 5x - 6 - 5{x^2} + 7{x^3} + 5x + 4 - 4{x^4} \\=(4x^4-4x^4)+(-7x^3+7x^3)+(6x^2-5x^2)+(-5x+5x)+(-6+4)\\= {x^2} - 2.\)
b) \(A(x) = B(x) + C(x) \Rightarrow C(x) = A(x) - B(x)\)
\(\begin{array}{l}C(x) = A(x) - B(x)\\ = 4{x^4} + 6{x^2} - 7{x^3} - 5x - 6 - ( - 5{x^2} + 7{x^3} + 5x + 4 - 4{x^4})\\ = 4{x^4} + 6{x^2} - 7{x^3} - 5x - 6 + 5{x^2} - 7{x^3} - 5x - 4 + 4{x^4}\\ =(4x^4+4x^4)+(-7x^3-7x^3)+(6x^2+5x^2)+(-5x-5x)+(-6-4)\\= 8{x^4} - 14{x^3} + 11{x^2} - 10x - 10\end{array}\)
\(P(x).A(x) = Q(x) \Rightarrow A(x) = Q(x):P(x)\)
Vậy \(A(x) = x - 1\).
a: f(a)=g(a)
=>5a-3=-1/2a+1
=>5,5a=4
=>\(a=\dfrac{4}{5.5}=\dfrac{8}{11}\)
b: f(b-2)=g(2b+4)
=>\(5\left(b-2\right)-3=-\dfrac{1}{2}\left(2b+4\right)+1\)
=>\(5b-13=-b-2+1=-b-1\)
=>6b=12
=>b=2
f(a) = g(a)
⇔ 5a - 3 = -a/2 + 1
⇔ 5a + a/2 = 1 + 3
⇔ 11a/2 = 4
⇔ 11a = 8
⇔ a = 8/11
Vậy a = 8/11 thì f(a) = g(a)
b) f(b - 2) = g(2b + 4)
⇔ 5.(b - 2) - 3 = -(2b + 4)/2 + 1
⇔ 5b - 10 - 3 = -b - 2 + 1
⇔ 5b + b = 1 + 13
⇔ 6b = 14
⇔ b = 7/3
Vậy b = 7/3 thì f(b - 2) = g(2b + 4)
Ta có: A=(x-4)-3(x+1)
=x-4-3x-3
=-2x-7=4
=>-2x=11 => x=-11/2
Vậy x=-11/2
\(A=\left(x-4\right)-3.\left(x+1\right)\)
\(\Rightarrow A=x-4-3x+3\)
\(\Rightarrow A=-2x-1\)
Mà A = 4
=> 4 = -2x - 1
=> 2x = -5
=> x = \(-\frac{5}{2}\)